Distribution and origin of oxygen-dependent and oxygen-independent forms of Mg-protoporphyrin monomethylester cyclase among phototrophic proteobacteria - Boldareva-Nuianzina, Ekaterina N; Bláhová, Zuzana; Sobotka, Roman; Koblízek, Michal (Applied and environmental microbiology, 2013)
Magnesium-protoporphyrin IX monomethylester cyclase is one of the key enzymes of the bacteriochlorophyll biosynthesis pathway. There exist two fundamentally different forms of this enzyme. The oxygen-dependent form, encoded by the gene acsF, catalyzes the formation of the bacteriochlorophyll fifth ring using oxygen, whereas the oxygen-independent form encoded by the gene bchE utilizes an oxygen atom extracted from water. The presence of acsF and bchE genes was surveyed in various phototrophic Proteobacteria using the available genomic data and newly designed degenerated primers. It was found that while the majority of purple nonsulfur bacteria contained both forms of the cyclase, the purple sulfur bacteria contained only the oxygen-independent form. All tested species of aerobic anoxygenic phototrophs contained acsF genes, but some of them also retained the bchE gene. In contrast to bchE phylogeny, the acsF phylogeny was in good agreement with 16S inferred phylogeny. Moreover, the survey of the genome data documented that the acsF gene occupies a conserved position inside the photosynthesis gene cluster, whereas the bchE location in the genome varied largely between the species. This suggests that the oxygen-dependent cyclase was recruited by purple phototrophic bacteria very early during their evolution. The primary sequence and immunochemical similarity with its cyanobacterial counterparts suggests that acsF may have been acquired by Proteobacteria via horizontal gene transfer from cyanobacteria. The acquisition of the gene allowed purple nonsulfur phototrophic bacteria to proliferate in the mildly oxygenated conditions of the Proterozoic era.
Keywords: Photosynthesis; bakteriální proteiny; Phylogeny; Protein Isoforms; Genome, Bacterial; Proteobacteria; genom bakteriální; oxygenasy; Oxygen; Oxygenases; kyslík; Bacterial Proteins; Cyanobacteria; fotosyntéza; protein - isoformy; fylogeneze; sinice